Oskarshamn herbarium (OHN) - Åke Rühling (GBIF Sweden, 2010)
This database contains information from the herbarium of Oskarshamn, Sweden. Specimens are collected from 1850 and later. The specimens are mainly collected from Sweden, but also from Austria, Norway, France and USA. The collection contains about 220 000 specimens of vascular plants.
Keywords: Växter; Plants; Occurrence; Specimen; Occurrence; OCCURRENCE; Biological Sciences; Biologi